Seamless micropore filling plating solution and filling method for thin-surface copper

By using a specific composition of plating solution and controlling the electroplating process in high-deep and aspect ratio micropores, seamless and uniform metal filling is achieved, and ultra-thin wheel bays are formed on the surface, solving the poor filling uniformity and waste of resources in the prior art. The problem of micropore filling quality and production efficiency have been improved.

CN119392324APending Publication Date: 2025-02-07FUZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411570399.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

When the prior art achieves uniform and seamless metal filling in high-deep and aspect ratio micropores, the filling uniformity is often poor due to random adsorption and desorption of chemical additives, and eventually a thicker metal layer is formed, reducing the efficiency of the polishing process, resulting in Waste of resources.

Method used

A thin-faced copper seamless micropore filling plating solution, including copper ions, acid electrolytes and bridge ions, is realized by controlling potential and current waveform during the filling process, combining the effects of non-ionic and ionic surfactants. Bottom-up filling and thin surface profile formation.

Benefits of technology

Achieve growth kinetic differences between micropores and surfaces, ensuring seamless fill in micropores, maintaining interpore uniformity, and obtaining ultra-thin surface profile layers, thereby improving micropore filling quality and reducing production costs .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392324A_ABST
    Figure CN119392324A_ABST
Patent Text Reader

Abstract

The invention relates to a seamless micropore filling plating solution for thin-surface copper and a filling method. The plating solution at least comprises copper ions, an acidic electrolyte, bridging ions and water, and at least contains one of chemical assistants such as a nonionic surfactant, an anionic surfactant, a cationic surfactant, a zwitterionic surfactant and quaternary ammonium salt dye. The method at least comprises the steps of infiltration of a sample to be filled, pre-plating and step current or voltage electroplating of one or more stages. According to the method, the uniformity of the interiors and the surfaces of the holes can be guaranteed while seamless filling is achieved, thin growth profiles are generated on the surfaces, and therefore the production cost is reduced while the micropore filling quality is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of high-end electronic manufacturing, and in particular to a seamless micro-pore filling plating solution and a filling method for thin-surface copper. Background Art

[0002] High-end electronic manufacturing products represented by chips and display screens require patterned metal layers as materials for electrical interconnection and signal transmission. Electroplating is the most widely used, efficient and economical method for achieving metal deposition in the above products. The process steps involved in the above products usually require: first forming micropores or grooves in media represented by silicon, glass and organic polymer materials; then, according to needs, optionally forming thin film structures such as barrier layers, adhesion layers and electroplating seed layers on the surface and sidewalls; then using electroplating technology to fill the required metal into the micropores or grooves; finally, using chemical mechanical polishing and other technologies to achieve surface thinning and flattening. As semiconductor devices gradually develop towards low cost, high reliability and high integration, the challenge of metal interconnection is to achieve uniform and seamless filling in high-density, high-aspect-ratio micropores.

[0003] In the prior art, chemical additives are added to the plating solution, and acceleration zones and inhibition zones are formed between the micropores and the surface by virtue of the effects of the chemical additives on the metal surface and the interactions between the chemical additives, thereby achieving seamless filling of micropores with a high aspect ratio. Although the related art supports the generation of growth kinetic differences between micropores with a high aspect ratio and the surface to achieve seamless filling, the filling uniformity is often poor due to the randomness of the adsorption and desorption sites of the chemical additives. A technical solution that has both seamlessness and high uniform plating capabilities will eventually form a thicker metal layer on the surface, which reduces the efficiency of the subsequent polishing process and causes a waste of resources. Therefore, a plating solution and method for seamless micropore filling of thin-surface copper are needed. Summary of the invention

[0004] The invention provides a seamless micropore filling plating solution and a filling method for thin-surface copper, which can achieve seamless filling while ensuring uniformity inside the hole and on the surface and generating a thinner growth profile on the surface.

[0005] The present invention adopts the following technical solutions: A seamless micro-pore filling plating solution for thin-surface copper, comprising the following components: Copper ion 10-90 g / L, acid electrolyte 1-100 g / L, bridging ion 20-200 mg / L, the balance is water balance; The copper ion source is copper sulfate, copper fluoroborate and copper methane sulfonate; The acidic electrolyte is one or more of sulfuric acid, fluoroboric acid and methanesulfonic acid; The bridging ion is one of chloride ion, bromide ion and iodide ion, and the source of the ion is corresponding sodium salt, potassium salt and anaerobic acid.

[0006] Furthermore, the filling plating solution also includes one or more of 0.01-10 g / L of nonionic surfactant, 0.1-20 mg / L of anionic surfactant, 1-100 mg / L of cationic surfactant, 1-50 mg / L of zwitterionic surfactant, and 1-100 mg / L of quaternary ammonium dye.

[0007] The nonionic surfactant includes but is not limited to polyethylene glycol, polypropylene glycol, fatty alcohol polyoxyethylene ether, polyoxyethylene alkylphenol ether, polyol polyether, polyoxyethylene sorbitan fatty acid ester and polyvinyl pyrrolidone; The anionic surfactant includes but is not limited to sodium 3-mercaptopropane sulfonate, sodium polydisulfide propane sulfonate, sodium allyl sulfonate, sodium thiazoline disulfide propane sulfonate, sodium 3-(benzothiazole-2-mercapto) propane sulfonate and sodium fatty alcohol polyoxyethylene ether sulfate; The cationic surfactant includes, but is not limited to, hexadecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, hexadecylpyridinium chloride, benzyltributylammonium bromide, cationic polyacrylamide, polydiallyldimethylammonium chloride and polyethyleneimine; The zwitterionic surfactants include but are not limited to dodecyl betaine, sodium N-lauroyl glutamate and 2-undecyl-N-carboxymethyl-hydroxyethyl imidazoline; The quaternary ammonium salt dyes include, but are not limited to, Janus green, fast green, crystal violet, ethyl violet, methylene violet, phenol red, neutral red, tetrazolium blue chloride, nitro tetrazolium blue chloride, tetranitro tetrazolium blue and iodonitrotetrazolium violet.

[0008] A method for seamless micropore filling of thin copper comprises the following steps: (1) The sample to be filled is fully contacted with the infiltration fluid in a vacuum chamber so that the infiltration fluid completely penetrates into each micropore of the sample to be filled; (2) Immerse the sample to be filled after immersion in the filling plating solution, apply a reduction potential of 0 V to −0.1 V to the sample to be filled for 5-10 min, and pre-plate the sample to be filled; (3) Applying a first constant or first step current or potential waveform to the sample to be filled to complete the first filling stage.

[0009] Furthermore, the method further comprises one or more of the following steps: Applying a second step current or potential waveform to the sample to be filled to complete a second filling stage, wherein the second filling stage is used to reduce the overshoot effect of the acceleration zone; Applying a third step current or potential waveform to the sample to be filled to complete a third filling stage, wherein the third filling stage is used to break through the strong inhibition effect of the orifice; A fourth constant or fourth stepped current or potential waveform is applied to the sample to be filled to complete a fourth filling stage, wherein the fourth filling stage is used to form a thin profile surface.

[0010] Further, the sample to be filled has one or more micropores; Further, the sample to be filled has a conductive layer extending from the bottom along the side wall to the surface; Furthermore, the micropore is a blind hole formed on the surface of the dielectric material by a method selected from the group consisting of dry etching, wet etching, laser ablation, laser induced etching, and mechanical drilling; Furthermore, the dielectric material is one of silicon, glass and organic polymer material.

[0011] Furthermore, the immersion fluid in step (1) is one or more of water, methanol, ethanol, isopropanol and filling plating solution; and the fluid is one of gas, liquid and gas-liquid mixture.

[0012] Furthermore, one or more auxiliary electrodes are configured in the filling plating solution to form a polarization circuit with the sample to be filled, and a reference electrode is configured to monitor and control the potential of the sample to be filled before, during and after filling.

[0013] Furthermore, the step current or potential waveform is one of the following changes: (1) Monotonic change of deposition current or potential; (2) Alternating changes in deposition current or potential and dissolution current or potential.

[0014] The beneficial effects of the present invention are: The present invention can not only create a growth kinetic difference between micropores and the surface to achieve bottom-up filling, but also maintain the uniformity and consistency of filling between micropores, and obtain an ultra-thin surface profile layer, thereby reducing production costs while ensuring the quality of micropore filling. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a slice diagram of the micropore filling result after the first filling stage of Example 1 is completed, provided in Example 1 of the present invention.

[0016] Figure 2 This is a slice diagram of the micropore filling results after completing the first to second filling stages of Example 1 provided in Example 1 of the present invention.

[0017] Figure 3This is a slice diagram of the micropore filling results after completing the first to third filling stages of Example 1 provided in Example 1 of the present invention.

[0018] Figure 4 This is a slice diagram of the micropore filling results after the first filling stage of Example 2 is completed, provided in Example 2 of the present invention.

[0019] Figure 5 This is a slice diagram of the micropore filling results after completing the first to second filling stages of Example 2 provided in Example 2 of the present invention.

[0020] Figure 6 This is a slice diagram of the micropore filling results after completing the first to third filling stages of Example 2 provided in Example 2 of the present invention.

[0021] Figure 7 This is a slice diagram of the micropore filling results after completing the first to fourth filling stages of Example 2 provided in Example 2 of the present invention.

[0022] Figure 8 This is a slice diagram of the micropore filling result obtained by using the plating solution provided in Comparative Example 1.

[0023] Fig. 9 This is a slice diagram of the micropore filling results obtained using the plating solution provided in Comparative Example 2.

[0024] Fig.10 This is a slice diagram of the micropore filling result obtained using the plating solution provided in Comparative Example 3.

[0025] Fig.11 This is a slice diagram of the micropore filling result obtained using the plating solution provided in Comparative Example 4.

[0026] Fig.12 This is a slice diagram of the micropore filling result obtained using the plating solution provided in Comparative Example 5. DETAILED DESCRIPTION

[0027] The following examples are further elaborations of the present invention. It should be noted that the descriptions of these embodiments are used to help understand the present invention, but do not constitute limitations of the present invention.

[0028] Example 1 (1) Filling plating solution composition: 250 g / L copper sulfate pentahydrate, 30 g / L sulfuric acid, 50 mg / L chloride ion (concentration is based on chloride ion, the raw material is hydrochloric acid), non-ionic surfactant (polyethylene glycol, 100 mg / L), anionic surfactant (sodium polydisulfide propane sulfonate, 1 mg / L), cationic surfactant (hexadecyltrimethylammonium chloride, 5 mg / L), quaternary ammonium salt dye (fast green, 5 mg / L), water (balance); (2) Filling process: The sample to be filled (glass substrate, blind hole with a pore size of 25±3μm and a depth of 225±10μm, made by laser induced etching method, with a continuous pre-deposited copper layer on the glass surface and in the hole) was immersed in the immersion fluid (50% ethanol aqueous solution), and the immersion fluid was fully infiltrated into the micropores of the sample using vacuum negative pressure (−0.1 MPa); the sample to be filled after immersion was transferred to the plating solution, and the sample to be filled was used as the cathode, the phosphor copper sheet as the anode, and copper / copper sulfate (saturated) as the reference electrode. A potential of −0.05 V (relative to the open circuit potential) was applied to the sample to be filled for pre-plating for 5 min, and then the filling was completed according to the conditions in Table 1: Table 1 Conditions of filling process in Example 1 (25±5°C)

[0029] Figure 1-Figure 3 The micropore filling result slice diagrams are respectively after completing the first filling stage, the first to second filling stage, and the first to third filling stage. It can be seen that the use of the electroplating solution and filling conditions of this embodiment can obtain a filling effect with no gaps in the hole and almost no copper on the surface.

[0030] Example 2 (1) Filling plating solution composition: copper methane sulfonate 300 g / L, methane sulfonic acid 20 g / L, chloride ion 50 mg / L (concentration is based on chloride ion, the raw material is sodium chloride), non-ionic surfactant (polyol polyether, 100 mg / L), anionic surfactant (sodium thiazolyl disulfide propane sulfonate, 2 mg / L), cationic surfactant (polyethyleneimine, 10 mg / L), zwitterionic surfactant (dodecyl betaine, 2 mg / L), quaternary ammonium dye (nitro blue tetrazolium chloride, 20 mg / L), water (balance); (2) Filling process: The sample to be filled (glass substrate, blind hole with a pore size of 25±3μm and a depth of 225±10μm, made by laser induced etching method, with a continuous pre-deposited copper layer on the glass surface and in the hole) is immersed in an immersion fluid (the filling plating solution of this embodiment), and the immersion fluid is fully infiltrated into the micropores by using a vacuum negative pressure (−0.1 MPa); the sample to be filled after immersion is transferred to the filling plating solution of this embodiment, and the sample to be filled is used as the cathode, the phosphor copper sheet is used as the anode, and copper / copper sulfate (saturated) is used as the reference electrode. A potential of −0.05V (relative to the open circuit potential) is applied to the sample to be filled for pre-plating for 5 min, and then the conditions in Table 2 are implemented to complete the filling.

[0031] Table 2 Conditions of filling process in Example 2 (25±5°C)

[0032] Figure 4-Figure 7 The slice diagrams of microvia filling results after the first filling stage, the first to second filling stage, the first to third filling stage, and the first to fourth filling stage are respectively completed by using this embodiment. The conditions of the embodiment of the present invention can obtain a filling effect from bottom to top with no gaps in the hole and thin copper on the surface.

[0033] Comparative Example 1 (1) The composition of the filling plating solution is the same as that of Example 1; (2) Filling process: The sample to be filled (glass substrate, blind hole with a pore size of 25±3μm and a depth of 225±10μm, made by laser induced etching method, with a continuous pre-deposited copper layer on the glass surface and in the hole) is immersed in the wetting fluid (filling plating solution), and the wetting fluid is fully infiltrated into the micropores by using vacuum negative pressure (−0.1 MPa); the sample to be filled after infiltration is transferred to the filling plating solution provided in this comparative example, and the sample to be filled is used as the cathode, the phosphor copper sheet as the anode, and copper / copper sulfate (saturated) as the reference electrode. A potential of −0.05 V (relative to the open circuit potential) is applied to the sample to be filled for pre-plating for 5 min, and then the filling is completed according to the conditions in Table 3. The filling results are shown in Table 3. Figure 8 .

[0034] Table 3 Conditions of filling process of comparative example 1 (25±5 ℃)

[0035] like Figure 8 As shown, in Comparative Example 1, in order to ensure that there are no gaps in the holes and uniformity between the holes during the filling process, a thicker metal layer will eventually be formed on the surface of the sample, which increases the workload of subsequent chemical mechanical polishing.

[0036] Comparative Example 2 (1) The composition of the filling plating solution is the same as that of Example 2; (2) Filling process: The preparation process before filling is the same as that in Comparative Example 1, and then the filling is completed according to the conditions in Table 4. The filling results are shown in Fig. 9 .

[0037] Table 4 Conditions of filling process of comparative example 2 (25±5 ℃)

[0038] like Fig. 9As shown, in Comparative Example 2, in order to inhibit the growth of the metal layer at the pore mouth and the surface, the adsorption of the chemical additive at the electrode interface and its interaction with the plating ions and / or bridging ions will produce a kinetic difference between the pore and the surface, so that the metal is preferentially filled from the bottom of the pore upward. However, due to the differences in the adsorption and desorption kinetics of the chemical additive, there will be differences in filling speed between different pores. As the filling time increases, some pores are filled first and continue to grow along the contour to form nodules on the surface.

[0039] contrast Figure 4 and Fig. 9 It can be seen that, compared with Comparative Example 2, Example 2 can ensure that the accelerated growth micropores will not be further filled by shortening the time of the first filling stage; contrast Figure 5 and Fig. 9 It can be seen that in Example 2, the alternating change of deposition and dissolution current is further increased through the second filling stage, so that the accelerated growth area is preferentially dissolved, achieving the effect of uniform filling in the pores; contrast Figure 6 and Fig. 9 It can be seen that Example 2 further passes through the third filling stage, and while ensuring uniform filling in the holes, continues to increase the current density to accelerate the desorption of the chemical additives, avoiding a slowdown in the plating rate due to excessive inhibition after filling to a certain height.

[0040] Comparative Example 3 (1) Filling plating solution composition: 250 g / L copper sulfate pentahydrate, 30 g / L sulfuric acid, 50 mg / L chloride ion (concentration is based on chloride ion, the raw material is hydrochloric acid), non-ionic surfactant (polyethylene glycol, 100 mg / L); (2) Filling process: The sample to be filled (glass substrate, blind hole with a pore size of 25±3μm and a depth of 225±10μm, made by laser induced etching method, with a continuous pre-deposited copper layer on the glass surface and in the hole) is immersed in the wetting fluid (filling plating solution), and the wetting fluid is fully infiltrated into the micropores by using vacuum negative pressure (−0.1MPa); the sample to be filled after infiltration is transferred to the plating solution provided in the embodiment of the present invention, and the sample to be filled is used as the cathode, the phosphor copper sheet is used as the anode, and copper / copper sulfate (saturated) is used as the reference electrode. A potential of −0.05 V (relative to the open circuit potential) is applied to the sample to be filled for pre-plating for 5 min, and then the conditions in Table 5 are implemented to complete the filling.

[0041] Table 5 Conditions of filling process of comparative example 3 (25±5 ℃)

[0042] Fig.10The micropore filling result obtained by using the plating solution provided in Comparative Example 3 shows that in the plating solution to which only a non-ionic surfactant is added, a filling layer of equal thickness growth is obtained, and slits are generated in the pores.

[0043] Comparative Example 4 The composition of the filling plating solution is: 250 g / L copper sulfate pentahydrate, 30 g / L sulfuric acid, 50 mg / L chloride ion (concentration is based on chloride ion, the raw material is hydrochloric acid), anionic surfactant (sodium polydisulfide propane sulfonate, 1 mg / L), cationic surfactant (hexadecyltrimethylammonium chloride, 5 mg / L), quaternary ammonium salt dye (fast green, 5 mg / L), water (balance); the filling process is the same as that of comparative example 3. Fig.11 The micropore filling result obtained by using the plating solution provided in Comparative Example 4 shows that in the plating solution without the presence of a non-ionic surfactant, a pre-sealed filling layer is obtained, and holes are generated in the holes.

[0044] Comparative Example 5 The composition of the filling plating solution is: 250 g / L copper sulfate pentahydrate, 30 g / L sulfuric acid, 50 mg / L chloride ion (concentration is calculated as chloride ion, the raw material is sodium chloride), cationic surfactant (cetylpyridinium chloride, 5 mg / L), quaternary ammonium dye (nitro blue tetrazolium chloride, 20 mg / L), water (balance); the filling process is the same as that of comparative example 3. Fig.12 The micropore filling result obtained by using the plating solution provided in Comparative Example 5 shows that in the plating solution containing only cationic surfactant and quaternary ammonium salt dye, an unevenly distributed filling layer is obtained, and both holes and seamless filling exist in the pores.

[0045] It can be seen from Examples 1-2 and Comparative Examples 1-5 that in order to simultaneously achieve the two technical features of high aspect ratio seamless gap filling and thin copper, at least the following conditions must be met: (1) Plating solution composition: It is necessary to rely on the interaction between the chemical additives used in the present invention. First, a cationic surfactant and / or quaternary ammonium dye that has a significant inhibitory ability on the pore mouth and surface copper deposition and can produce a significant growth dynamics difference at different depths in the pore (to facilitate bottom-up filling) is required. Secondly, a non-ionic surfactant with strong inhibitory ability and reach ability is required to stabilize the inhibitory effect. In addition, anionic surfactants and / or zwitterionic surfactants are also required to further improve efficiency and filling effect; (2) Filling process: It is necessary to control the uniformity of inter-pore filling and surface growth. Due to the differences in the adsorption and desorption of the chemical additives used at different sites on the surface, there will be differences in growth dynamics between the pores, causing some pores to be filled first and further form nodules. By alternating between deposition and dissolution, the areas with excessive growth can be dissolved first, achieving the effect of uniform filling in the pores. On the other hand, the effect of chemical additives also causes the micropores to be overly suppressed after being filled to a certain height, resulting in a slow plating rate. Therefore, it is necessary to increase the current density in the later stage of filling to accelerate the desorption of chemical additives.

[0046] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention.

Claims

1. A seamless microporous filling plating solution for thin-surface copper, characterized in that: It includes the following components: copper ion 10-90 g / L, acid electrolyte 1-100 g / L, bridging ion 20-200 mg / L, and the balance is water balance; The copper ion is selected from one of copper sulfate, copper fluoroborate and copper methane sulfonate; The acidic electrolyte includes one of sulfuric acid, fluoroboric acid and methanesulfonic acid; The bridging ion comprises one of chloride ion, bromide ion and iodide ion, and the source of the ion is corresponding sodium salt, potassium salt and oxygen-free acid.

2. The seamless microporous filling plating solution for thin-surface copper according to claim 1, characterized in that: The filling plating solution further comprises one or more of 0.01-10 g / L of nonionic surfactant, 0.1-20 mg / L of anionic surfactant, 1-100 mg / L of cationic surfactant, 1-50 mg / L of zwitterionic surfactant, and 1-100 mg / L of quaternary ammonium dye; The nonionic surfactant includes one or more of polyethylene glycol, polypropylene glycol, fatty alcohol polyoxyethylene ether, polyoxyethylene alkylphenol ether, polyol polyether, polyoxyethylene sorbitan fatty acid ester and polyvinyl pyrrolidone; The anionic surfactant includes one or more of sodium 3-mercaptopropane sulfonate, sodium polydisulfide propane sulfonate, sodium allyl sulfonate, sodium thiazoline disulfide propane sulfonate, sodium 3-(benzothiazole-2-mercapto) propane sulfonate and sodium fatty alcohol polyoxyethylene ether sulfate; The cationic surfactant includes one or more of cetyltrimethylammonium chloride, dodecyltrimethylammonium bromide, cetylpyridinium chloride, benzyltributylammonium bromide, cationic polyacrylamide, polydiallyldimethylammonium chloride and polyethyleneimine; The amphoteric surfactant includes one or more of lauryl betaine, sodium N-lauroyl glutamate and 2-undecyl-N-carboxymethyl-hydroxyethyl imidazoline; The quaternary ammonium salt dye includes one or more of Janus green, fast green, crystal violet, ethyl violet, methylene violet, phenol red, neutral red, tetrazolium blue chloride, nitro tetrazolium blue chloride, tetranitro tetrazolium blue and iodonitrotetrazolium violet.

3. A method for seamless micropore filling of thin copper, characterized in that: The following steps are involved: (1) The sample to be filled is fully contacted with the infiltration fluid in a vacuum chamber so that the infiltration fluid completely penetrates into each micropore of the sample to be filled; (2) Immerse the sample to be filled after immersion in the filling plating solution, apply a reduction potential of 0 V to −0.1 V to the sample to be filled for 5-10 min, and pre-plate the sample to be filled; (3) Applying a first constant or first step current or potential waveform to the sample to be filled to complete the first filling stage.

4. The method for seamless micropore filling of thin copper according to claim 3, characterized in that: Also include one or more of the following steps: Applying a second step current or potential waveform to the sample to be filled to complete the second filling stage; Applying a third step current or potential waveform to the sample to be filled to complete the third filling stage; A fourth constant or fourth step current or potential waveform is applied to the sample to be filled to complete the fourth filling stage.

5. The method for seamless micropore filling of thin copper according to claim 3, characterized in that: The sample to be filled has one or more micro-holes; the sample to be filled has a conductive layer extending from the bottom along the side wall to the surface; The micropores are blind holes formed on the surface of a dielectric material by dry etching, wet etching, laser ablation, laser induced etching, or mechanical drilling; the dielectric material is one of silicon, glass, and an organic polymer material.

6. The method for seamless micropore filling of thin copper according to claim 3, characterized in that: The immersion fluid in step (1) is one or more of water, methanol, ethanol, isopropanol and filling plating solution; The fluid is one of gas, liquid and a gas-liquid mixture.

7. A method for seamless micropore filling of thin copper according to any one of claims 3 to 4, characterized in that: One or more auxiliary electrodes are configured in the filling plating solution to form a polarization loop with the sample to be filled, and a reference electrode is configured to monitor and control the potential of the sample to be filled before, during and after filling.

8. A method for seamless micropore filling of thin copper according to any one of claims 3 to 4, characterized in that: The step current or potential waveform is one of the following changes: (1) Monotonic change of deposition current or potential; (2) Alternating changes in deposition current or potential and dissolution current or potential.